The Jacobson Radical of the Endomorphism Semiring of P.Q.- Principal Injective Semimodules (Baghdad Science Journal, 2020)
In this work, we introduced the Jacobson radical (shortly Rad (Ș)) of the endomorphism semiring Ș = ( ), provided that is principal P.Q.- injective semimodule and some related concepts, we studied some properties and added conditions that we needed. The most prominent result is obtained in section three-If is a principal self-generator semimodule, then (ȘȘ) = W(Ș).Subject Classification: 16y60